Hubungan Kekurangan Energi Kronis (Kek) Dengan Kejadian Anemia Pada Ibu Hamil Dengan Studi Cross-Sectional - Jumriana Ibriani; Husnul Hatima; Arniati Arniati (LPPM STIKES Marendeng Majene, 2026)
Chronic Energy Deficiency (CED) is caused by long-term nutritional intake imbalance. As a sign of malnutrition, it is closely related to anemia in pregnant women. This study analyzed the relationship between CED and anemia incidence among pregnant women at Tamalanrea Community Health Center, Makassar. Using an analytical survey with a cross-sectional design, 60 respondents were selected through purposive sampling. The chi-square test yielded a p-value of 0.049 (p < 0.05), indicating a significant relationship between CED and anemia in pregnant women. Therefore, healthcare workers should strengthen continuous Information, Education, and Communication (IEC) and use a cross-sectoral approach to monitor and improve the nutritional health of pregnant women